Flow-Induced Pulsation and Vibration in Hydroelectric Machinery Engineer’s Guidebook for Planning, Design and Troubleshooting - Dörfler, Peter. (Springer London : Imprint: Springer, 2013)
Since the 1970’s, an increasing amount of specialized research has focused on the problems created by instability of internal flow in hydroelectric power plants. However, progress in this field is hampered by the interdisciplinary nature of the subject, between fluid mechanics, structural mechanics and hydraulic transients. Flow-induced Pulsation and Vibration in Hydroelectric Machinery provides a compact guidebook explaining the many different underlying physical mechanisms and their possible effects.   Typical phenomena are described to assist in the proper diagnosis of problems and various key strategies for solution are compared and considered with support from practical experience and real-life examples. The link between state-of the-art CFD computation and notorious practical problems is discussed  and quantitative data is provided on  normal levels of vibration and pulsation so realistic limits can be set for future projects. Current projects are also addressed as the possibilities and limitations of reduced-scale model tests for prediction of prototype performance are explained.   Engineers and project planners struggling with practical problems will find Flow-induced Pulsation and Vibration in Hydroelectric Machinery to be a comprehensive and convenient  reference covering key topics and ideas across a range of relevant disciplines.